Modified team based learning: Its feasibility and effectiveness in learning gross anatomy - G Vinitha; M Lakshmidevi; Priya Ranganath (Wolters Kluwer Medknow Publications, 2018)
Aims and Objectives: Knowledge of human anatomy with clear understanding of its clinical applications is important for producing good quality medical graduates. With many newer student centered teaching techniques coming up modified team based learning has been analyzed in this study. Aims: To know 1] Feasibility and utility of modified team based learning [MTBL] in gross anatomy with clinical aspects. 2] Effectiveness of MTBL in understanding gross anatomy and students approach to MTBL. Material and methods: Two traditional gross anatomy lectures were replaced by two MTBL sessions. 250 first year medical students were randomly grouped into 35 teams with 7 students each. During each session, students went through the steps of MTBL - pre class preparation, individual readiness assurance test [IRAT], group readiness assurance test [GRAT] and application exercise. A five point Likert scale questionnaire was given to students to assess their opinion about MTBL activities. After 15 days, a surprise test [ST] was given to assess effectiveness of MTBL sessions. Results: A significant positive correlation was observed between individual student's performance on IRAT and ST, between individual performances from session-1 to session-2, as well as in group performances in first and second session. 57% students strongly agreed that their performance improved working as a team than individually and increased student's ability to use their critical and analytical skills. Conclusion: This study shows that MTBL is feasible and approachable to students. MTBL acts as an important tool in medical education as it has the ability to develop self-learning, higher reasoning skills and team work skills.